Preliminary effects of risk-adapted PSA screening for prostate cancer after integrating PRS-specific and age-specific variation - Liu, Xiaomin; Duan, Hongyuan; Liu, Siwen; Zhang, Yunmeng; Ji, Yuting; Zhang, Yacong; Feng, Zhuowei; Li, Jingjing; Liu, Ya; Gao, Ying; Wang, Xing; Zhang, Qing; et al. (Frontiers in Genetics, 2024)
Background: Although the risk of prostate cancer (PCa) varies across different ages and genetic risks, it's unclear about the effects of genetic-specific and age-specific prostate-specific antigen (PSA) screening for PCa.Weighed and unweighted polygenic risk scores (PRS) were constructed to classify the participants from the PLCO trial into low-or high-PRS groups. The age-specific and PRS-specific cutoff values of PSA for PCa screening were determined with time-dependent receiver-operatingcharacteristic curves and area-under-curves (tdAUCs). Improved screening strategies integrating PRSspecific and age-specific cut-off values of PSA were compared to traditional PSA screening on accuracy, detection rates of high-grade PCa (Gleason score ≥7), and false positive rate.Results: Weighted PRS with 80 SNPs significantly associated with PCa was determined as the optimal PRS, with an AUC of 0.631. After stratifying by PRS, the tdAUCs of PSA with a 10-year risk of PCa were 0.818 and 0.816 for low-and high-PRS groups, whereas the cut-off values were 1.42 and 1.62 ng/ml, respectively. After further stratifying by age, the age-specific cut-off values of PSA were relatively lower for low PRS (1.42, 1.65, 1.60, and 2.24 ng/ml for aged <60, 60-64, 65-69, and ≥70 years) than high PRS (1.48, 1.47, 1.89 and 2.72 ng/ml). Further analyses showed an obvious interaction of positive PSA and high PRS on PCa incidence and mortality. Very small difference in PCa risk were observed among subgroups with PSA(-) across different age and PRS, and PCa incidence and mortality with PSA(+) significantly increased as age and PRS, with highest risk for high-PRS/PSA(+) in participants aged ≥70 years [HRs(95%CI): 16.00 (12.62-20.29) and 19.48(9.26-40.96)]. The recommended screening strategy reduced 12.8% of missed PCa, ensured high specificity, but not caused excessive false positives than traditional PSA screening.Conclusions: Risk-adapted screening integrating PRS-specific and age-specific cut-off values of PSA would be more effective than traditional PSA screening.